2018
DOI: 10.1080/19932820.2017.1422666
|View full text |Cite
|
Sign up to set email alerts
|

The importance of perfusion index monitoring in evaluating the efficacy of stellate ganglion blockage treatment in Raynaud’s disease

Abstract: Stellate ganglion blockage (SGB) is a method used for treating Raynaud’s phenomenon (RP). This study primarily aimed to determine whether the perfusion index (PI) can be used an alternative to Horner’s signs in evaluating the efficacy of SGB in patients diagnosed with RP. In a total of 40 patients, aged 18–65 years and diagnosed with primary RP, SGB was applied for 5 days on the same side with the 2-finger method, using 6 mL of 5% levobupivacaine at the 7th cervical vertebra level. The PI values were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…A previous study measured the PI values at relatively wide intervals (10 min), but we used shorter intervals (5 min). Although there were no mentions of the PI ratio, previous studies have compared the baseline PI with the PI value after 5 min and reported its statistical significance 19 21 . In addition, it was confirmed that the PI at 5 min after the SCBPB was the fastest reference point for the change in the PI as a result of AUROC analysis, and the AUROCs were not significantly different across time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study measured the PI values at relatively wide intervals (10 min), but we used shorter intervals (5 min). Although there were no mentions of the PI ratio, previous studies have compared the baseline PI with the PI value after 5 min and reported its statistical significance 19 21 . In addition, it was confirmed that the PI at 5 min after the SCBPB was the fastest reference point for the change in the PI as a result of AUROC analysis, and the AUROCs were not significantly different across time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Mowafi and colleagues [22] showed that PI is a reliable measure for the intravascular injection of epinephrine during epidural anesthesia. Some reports have described the use of PI in various conditions, namely, for pain assessment in critically ill patients, at the onset of stellate ganglion block, in lumbar and thoracic sympathectomy, or for prediction of the success of brachial plexus or sciatic nerve blocks [21,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Mowafi and colleagues [18] demonstrated that the PI is a reliable measure for the intravascular injection of epinephrine during epidural anesthesia. Some reports have indicated that the PI can be used for pain assessment in patients with critical illnesses, at the onset of stellate ganglion block, in lumbar and thoracic sympathectomy, or for predicting the success of brachial plexus, sciatic, or lumbar transforaminal blocks [20,23,24,25,26,27].…”
Section: Discussionmentioning
confidence: 99%